Translocation of pesticides in coconut palm by endotherapy with the addition of different adjuvants - Ferreira, Jordana Alves; Ferreira, Joana Maria Santos; Talamini, Viviane; Lins, Paulo Manoel Pontes; Farias, Samuel Christian Cohen; Bottoli, Carla Beatriz Grespan (Ciência e Natura, 2020)
Commercial pesticides were selected, mixed and applied in coconut stems (Cocos nucifera Linn.) by endotherapy with various adjuvants. Tissue samples from the coconut stem were collected at different heights and days, and subjected to extraction and analysis by modified QuEChERS (“Quick, Easy, Cheap, Effective, Rugged and Safe") and UHPLC-MS/MS (ultra-high-performance liquid chromatography–tandem mass spectrometry). The translocations of 3-hydroxy-carbofuran, carbendazim, carbofuran, difenoconazole, imidacloprid, thiabendazole, thiamethoxam, thiophanate-methyl and spirodiclofen, using salts, citric acid and organosilicones as adjuvants, were evaluated and compared 2 and 30 days after the applications. The results showed that each pesticide had a different translocation profile, modified by the presence of the adjuvants. The most significant modifications were obtained using organosilicones, which enhanced the translocation process by 40% for most pesticides, followed by acidification (30%) and the addition of salts (22%).